TGF-β activation by bone marrow-derived thrombospondin-1 causes Schistosoma- and hypoxia-induced pulmonary hypertension - Kumar, Rahul; Mickael, Claudia; Kassa, Biruk; Gebreab, Liya; Robinson, Jeffrey C.; Koyanagi, Daniel E.; Sanders, Linda; Barthel, Lea; Meadows, Christina; Fox, Daniel; Irwin, David; Li, Min; et al. (Nature communications, 2017)
Pulmonary arterial hypertension (PAH) is an obstructive disease of the precapillary pulmonary arteries. Schistosomiasis-associated PAH shares altered vascular TGF-β signalling with idiopathic, heritable and autoimmune-associated etiologies; moreover, TGF-β blockade can prevent experimental pulmonary hypertension (PH) in pre-clinical models. TGF-β is regulated at the level of activation, but how TGF-β is activated in this disease is unknown. Here we show TGF-β activation by thrombospondin-1 (TSP-1) is both required and sufficient for the development of PH in Schistosoma -exposed mice. Following Schistosoma exposure, TSP-1 levels in the lung increase, via recruitment of circulating monocytes, while TSP-1 inhibition or knockout bone marrow prevents TGF-β activation and protects against PH development. TSP-1 blockade also prevents the PH in a second model, chronic hypoxia. Lastly, the plasma concentration of TSP-1 is significantly increased in subjects with scleroderma following PAH development. Targeting TSP-1-dependent activation of TGF-β could thus be a therapeutic approach in TGF-β-dependent vascular diseases. Thrombospondin-1 (TSP-1) activates latent TGF-β in the extracellular matrix. Here the authors show that inappropriate activation of latent TGF-β in murine, bovine and human lung by monocyte-produced TSP-1 causes pulmonary hypertension, and that interference with the activation process prevents disease development.